PERKEMBANGAN TAFSIR FALSAFI DALAM RANAH PEMIKIRAN ISLAM - Syafieh, Syafieh (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2017)
This article will explain about the development of philosophical interpretation from classical to modern era. The emergence of the medieval philosophical interpretation has provided a new insight into the development of interpretation. The existence of this style of philosophical interpretation is also the